THE RELATIONSHIP BETWEEN PERSONAL HYGIENE AND THE INCIDENCE OF SKIN DISEASES IN LORONG MESJID LK. IV BAGAN DELI BELAWAN - Sianturi, Anggina Cucu Khetri; Nanda, Meutia; Nasution, Azzahra Ramadhana; Saragih, Dini Azila; Sagala, Rahmadani (HEARTY, 2025)
Skin disease is a condition or disorder that affects the human skin. Factors that cause skin diseases include an unclean environment and inadequate personal hygiene behaviour. Poor personal hygiene behaviour can increase the risk of developing skin diseases. This study aims to find the relationship between personal hygiene and the incidence of skin diseases in the population of Lorong Mesjid Lingkungan IV Bagan Deli Belawan. This study is quantitative and uses an analytical approach with a cross-sectional design. The population consisted of all people living in Lorong Mesjid Lingkungan IV Bagan Deli Belawan, with a total population of 1,963 people. This study involved a sample of 92 people selected using simple random sampling method and Lemeshow's formula. Data were collected through observation sheets and questionnaires filled out through interviews with respondents. Data were analysed using chi-square. The results showed that clothing hygiene, hand hygiene, towel use, and frequency of bathing had a significant relationship with the incidence of skin diseases, with a p-value of 0.001 each. Therefore, there was a significant association between the incidence of skin diseases and clothing hygiene, hand and nail hygiene, towel hygiene, and frequency of bathing. However, no statistically significant relationship was found between the use of footwear and the incidence of skin diseases. Therefore, residents in the coastal area of Lorong Mesjid Lingkungan IV Bagan Deli Belawan are advised to increase attention to personal hygiene, including skin hygiene, such as clothing care, hand and nail hygiene, towel hygiene, as well as increasing the frequency of bathing, and using footwear when doing activities outside the home.